Cytokine and Phenotypic Cell Profiles of Leishmania infantum Infection in the Dog. - Maia, Carla (2021)
Leishmaniasis has reemerged in recent years showing a wider geographic distribution and increased global incidence of human and canine disease than previously known. Dogs are the main domestic/peridomestic reservoir hosts of zoonotic visceral leishmaniasis caused by Leishmania infantum. Since the evolution of leishmaniasis and clinical appearance is a consequence of complex interactions between the parasite and host immune response, a profound knowledge about the immune profile developed in dog's infection is crucial for vaccine and immunomodulatory therapy design. The main goal of this paper is to compile the recent advances made on cytokine and phenotypic cell profiles in different tissues and organs of dogs infected with L. infantum. This paper also stressed that the knowledge of the immune responses developed, namely, in liver, lymph node, and spleen is very limited. All data emphasizes that more research on canine leishmaniasis is necessary for the development of new and efficacious tools to control zoonotic leishmaniasis.